Decision Making Behaviour on the Choice of UK Business School: A Chinese Cultural Perspective - Xun, Jiyao (2006)
This study aims to contribute to the knowledge of marketing international higher education underpinned by marketing theories and provide managerial implications for education marketers as well. This is carried out with specific reference to Chinese students' choice behaviour of UK business school. The purpose of this dissertation is to systematically examine and evaluate literature in higher education service, decision making theories and Chinese culture to propose theoretical models that integrates the different antecedents and consequences of Chinese cultural that impact on decisions being made on choice of a UK business school. Proposed models are developed based on deduction derived from the literature on the decision making and Chinese cultural value system. In addition, the researcher empirically tests these frameworks on Chinese students' choice behaviour and provides managerial implications for both UK higher educational institutions in general and business school management and marketers as well.